우측 대장에서 대장내시경 후굴에 의한 추가적인 폴립 발견율 - 김흥업; Heung Up Kim; 부선진; Sun Jin Boo; 나수영; Soo Young Na; 송현주; Hyun Joo Song (The Korean journal of gastroenterology, 2015)
Background/Aims: There have been several studies showing that retroflexion (RF) in the right colon (RC) could reduce the polyp miss rate of proximal colon during colonoscopy. This study was conducted to evaluate the additional benefit of RF technique in the RC. Methods: Patients who underwent colonoscopy from May 2008 to April 2011 were enrolled in the study. Data were obtained by retrospectively reviewing the medical records. RF was attempted in every patients undergoing colonoscopy since May 2008 except in cases of small RC vault, co-morbidity, severe diverticulosis, failed RF despite two trials, complaints of severe abdominal pain, or time burden. At first, RC was examined under direct vision. It was then examined by RF to detect missed polyps during the initial observation. Finally, the RC was re-examined with direct view. Results: The cumulative RF success rate in the RC was 78.84% (1,805 of 2,319). The RF success rate increased with the number of cases (50% at 160 cases, 70% at 400 cases, and reached near 90% over 1,000 cases). Few polyps (4.88%) were detected only with RF and the additional adenoma detection rate was 3.32%. The additional polyp/adenoma detection rates were higher in the old age group (p＜0.01). There were no RF associated perforation or severe complication. Conclusions: Using RF examination, additional 4.88% of polyps could be detected in the RC. This technique could be a useful and safe method to detect hidden polyp during colonoscopy.